Systemowe rozwiązania służące ochronie środowiska naturalnego w wybranych krajach Unii Europejskiej na przykładzie zużytych baterii i akumulatorów - Całek, Anna (Wydawnictwo Akademii Ekonomicznej im. Oskara Langego we Wrocławiu, 2008)
Considering the matter of the collection of waste batteries and accumulators, one has to refer to international experience in this topic. Belgium, Germany, the Netherlands, France, Denmark and Poland may be found among the countries that have introduced interesting solutions in this area. On the basis of the solutions presented in the article one has to admit that the framework of modern waste management concerns detaching hazardous waste, therein waste batteries and accumulators, from the stream of communal waste and directing them into the system for utilization of wastes. The experience of the EU-15 shows that the existence of permanent collection points of waste batteries and accumulators has been widely accepted and well organized informative action on the principles of collecting hazardous waste was successful. The EU countries are well aware of the fact that rational waste management is necessary and therefore the changes that have been lately introduced in the European legislation concerning environment protection have constrained possibilities of production and trade of cells containing hazardous elements. The countries merely beginning to implement legislation of this kind into their economies may gain high benefits by adopting similar solutions. (original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2008; nr 1191, s. 41-51